2022
DOI: 10.1021/acs.jctc.2c00746
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Reference Spin-Flip Time-Dependent Density Functional Theory for Accurate X-ray Absorption Spectroscopy

Abstract: It is demonstrated that the challenging core hole-particle (CHP) orbital relaxation for core electron spectra can be readily achieved by the mixed-reference spin-flip (MRSF)-TDDFT.With the additional scalar relativistic effects on K-edge excitation energies of 24 second-and 17 third-row molecules, the particular ∆CHP-MRSF(R) exhibited near perfect predictions with RMSE ∼ 0.5 eV, featuring a median value of 0.3 and and an interquartile range of 0.4.Overall, the CHP effect is 2 ∼ 4 times stronger than relativist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 77 publications
(143 reference statements)
0
25
0
Order By: Relevance
“…This restricts the MRSF-TDDFT excitation space from unwanted occupied orbitals. This simple strategy exhibited near-perfect predictions with RMSE ∼ 0.5 eV, featuring a median value of 0.3 and an interquartile range of 0.4 for K-edge excitation energies of 24 s- and 17 third-row molecules …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This restricts the MRSF-TDDFT excitation space from unwanted occupied orbitals. This simple strategy exhibited near-perfect predictions with RMSE ∼ 0.5 eV, featuring a median value of 0.3 and an interquartile range of 0.4 for K-edge excitation energies of 24 s- and 17 third-row molecules …”
Section: Methodsmentioning
confidence: 99%
“…Our model is based on a combination of the electrostatic embedding QM/MM method, used to equilibrate a water droplet around the molecule of interest, and mixed-reference spin-flip time-dependent density functional theory (MRSF-TDDFT) coupled to QM/MM to extract X-ray spectroscopy. MRSF-TDDFT has been recently shown to be able to efficiently and accurately extract XAS, with errors that are within 1 eV of the experimental spectra . In addition, an MRSF-TDDFT/MM coupling was shown to lead to accurate excited-state nonadiabatic dynamics of thymine in water …”
Section: Introductionmentioning
confidence: 99%
“…42 The doubles are critical components for the accurate descriptions of excited states, bond breakings, conical intersections, etc., which significantly expands the applicability of MRSF-TDDFT. (6) Recently, it has been demonstrated that the high spin triplet reference of MRSF-TDDFT provides a simple way of ensuring core-hole relaxation for accurate XAS (X-ray absorption), 43 which has been one of the main difficulties of LR-TDDFT. Detailed discussions can be found later in the main text.…”
mentioning
confidence: 99%
“…In the case of LR-TDDFT, the corresponding accuracy is crude, with errors as large as ∼10 eV for second-period elements like C, N, O, and F, and even larger errors for heavier elements. With the additional scalar relativistic effects on K-edge excitation energies of 24 s- and 17 third-row molecules, on the other hand, the particular ΔCHP-MRSF­(R) exhibited near-perfect predictions with root-mean-square error (RMSE) ≈ 0.5 eV, featuring a median of 0.3 and an interquartile range of 0.4 . The XAS of valence excited states can also be calculated by the same protocol.…”
mentioning
confidence: 99%
See 1 more Smart Citation